Microscale surface texturing on nonplanar surface of diffusion lens for anti-glare LED light. (1st June 2022) - Bang, Hyun Chul; Lee, Sang Woo; Jang, Woong Ki; Kim, Byeong Hee; Seo, Young Ho
Abstract: In this study, we present the fabrication technique and characterization results of a concave-bottom rod lens (CB-RL) covered with microstructures to diffuse the Light-emitting diode (LED) light for anti-glare. The spherical concave bottom of the rod lens was designed based on a basic refraction theory and was fabricated by using the hyper-elastic deformation characteristics of polydimethylsiloxane film to form microstructures on the nonplanar surface. The rod lens mold and microstructure mold were prepared via the metal cutting process and photoresist reflowing process, respectively. In the experimental study, a CB-RL with and without microstructures was fabricated and compared. A CB-RL mounted on an LED effectively changed the isomeric luminous intensity profile into a batwing-shape profile. The reduction in discomfort glare induced by a single LED was characterized by comparing the uniformities of the luminous intensity between the bare and proposed lens-mounted LEDs. The full width half maximum (FWHM) value of the luminous intensity was increased from 50.9% to 71.4%, and the maximum-to-minimum ratio of the luminous intensity was reduced from 3.91 to 1.94. For a light bulb consisting of eight LEDs, the FWHM value and maximum-to-minimum ratio of the luminous intensities were improved from 38.0% to 55.0% and from 10.96 to 6.96, respectively.